Overview of fungi and mycotoxin contamination in Capsicum pepper and in Its derivatives - Costa, Jéssica; Rodríguez, Rodrigo; García-Cela, Esther; Medina, Angel; Magan, Naresh; Lima, Nelson; Battilani, Paola; Santos, Cledir (MDPI, 2019)
Capsicum products are widely commercialised and consumed worldwide. These substrates present unusual nutritional characteristics for microbial growth. Despite this, the presence of spoilage fungi and the co-occurrence of mycotoxins in the pepper production chain have been commonly detected. The main aim of this work was to review the critical control points, with a focus on mycotoxin contamination, during the production, storage and distribution of Capsicum products from a safety perspective; outlining the important role of ecophysiological factors in stimulating or inhibiting mycotoxin biosynthesis in these food commodities. Moreover, the human health risks caused by the ingestion of peppers contaminated with mycotoxins were also reviewed. Overall, Capsicum and its derivative-products are highly susceptible to contamination by mycotoxins. Pepper crop production and further transportation, processing and storage are crucial for production of safe food.
Keywords: aflatoxins; chilli; mycotoxins; ochratoxin A; pepper; spoilage fungi